A new structural motif for cadmium dithiocarbamates: crystal structures and hirshfeld surface analyses of homoleptic zinc and cadmium morpholine dithiocarbamates - Ahmad, Jimmy; How, Fiona Ni Foong; Abdul Halim, Siti Nadiah; Jotani, Mukesh M.; Lee, Seemun; Tiekink, Edward R.T. (Walter de Gruyter, 2019)
The crystal and molecular structures of two homoleptic morpholine-derived dithiocarbamates of zinc, binuclear {Zn[S2CN(CH2CH2)2O)2]2}2 (1), and cadmium, one-dimensional coordination polymer {Cd[S2CN(CH2CH2) 2O)2]2}2 (2), are described. In 1, a centrosymmetric binuclear molecule is found as there are equal numbers of chelating and bidentate bridging dithiocarbamate ligands; weak transannular Zn · · · S interactions are found within the resultant eight-membered { · · · SCSZn}2 ring which has the form of a chair. The resultant 4 + 1 S5 donor set is highly distorted with the geometry tending towards a squarepyramid. By contrast, a square-planar geometry is found in centrosymmetric 2 defined by symmetrically chelating dithiocarbamate ligands. The presence of Cd · · · S secondary bonding in the crystal of 2 leads to a distorted 4 + 2 S6 octahedron and a linear coordination polymer, which is unprecedented in the structural chemistry of cadmium dithiocarbamates. The analyses of the Hirshfeld surfaces for 1 and 2 show the dominance of H · · · H, S · · · H/H · · · S and O · · · H/H · · · O contacts to the surface, i.e. contributing around 90 and 80%, respectively.